Independent Monte-Carlo dose calculation for MLC based CyberKnife radiotherapy. (18th December 2017) - Mackeprang, P-H; Vuong, D; Volken, W; Henzen, D; Schmidhalter, D; Malthaner, M; Mueller, S; Frei, D; Stampanoni, M F M; Dal Pra, A; Aebersold, D M; Fix, M K; et al.
Abstract: This work aims to develop, implement and validate a Monte Carlo (MC)-based independent dose calculation (IDC) framework to perform patient-specific quality assurance (QA) for multi-leaf collimator (MLC)-based CyberKnife ® (Accuray Inc., Sunnyvale, CA) treatment plans. The IDC framework uses an XML-format treatment plan as exported from the treatment planning system (TPS) and DICOM format patient CT data, an MC beam model using phase spaces, CyberKnife MLC beam modifier transport using the EGS++ class library, a beam sampling and coordinate transformation engine and dose scoring using DOSXYZnrc. The framework is validated against dose profiles and depth dose curves of single beams with varying field sizes in a water tank in units of cGy/Monitor Unit and against a 2D dose distribution of a full prostate treatment plan measured with Gafchromic EBT3 (Ashland Advanced Materials, Bridgewater, NJ) film in a homogeneous water-equivalent slab phantom. The film measurement is compared to IDC results by gamma analysis using 2% (global)/2 mm criteria. Further, the dose distribution of the clinical treatment plan in the patient CT is compared to TPS calculation by gamma analysis using the same criteria. Dose profiles from IDC calculation in a homogeneous water phantom agree within 2.3% of the global max dose or 1 mm distance to agreement to measurements for all except the smallest field size. Comparing the film measurement to calculated dose, 99.9% of all voxels pass gamma analysis, comparing dose calculated by the IDC framework to TPS calculated dose for the clinical prostate plan shows 99.0% passing rate. IDC calculated dose is found to be up to 5.6% lower than dose calculated by the TPS in this case near metal fiducial markers. An MC-based modular IDC framework was successfully developed, implemented and validated against measurements and is now available to perform patient-specific QA by IDC.